4-(1-Adamantylmethyl)-N-(2-chloro-9-isopropyl-9H-purin-6-yl)aniline - Rouchal, Michal (International Union of Crystallography, 2009)
The asymmetric unit of the title compound, C(25)H(30)ClN(5), consists of two molecules with slightly different geometrical parameters. The dihedral angles between the purine and benzene rings are 39.54 (5) and 23.69 (5)° in the two molecules. The adamantane cages consist of three fused cyclohexane rings in classical chair conformations, with C—C—C angles in the range 108 (2)–111 (2)°. In the crystal, molecules are linked into dimers via two N—H⋯N hydrogen bonds.